The Coffee Shop New Retail Business Model - Noneng Nurjanah; Dera Thorfiani (Research Synergy Foundation, 2022)
New retail is an innovative business model combining online and offline (O2O) shopping experiences (Alibaba Gorup, 2018) and is discovering how to adapt to the digital transformation. Several factors that could affect consumer experience when shopping online include ease of accessing and using the web, Hedonic and Utilitarian Features, Convenience, personalization, social interaction, and compatibility on various devices. The study aims to measure the relationship between the new retail business model dimension: customer, convenience, and communication to customer experience. This research identifies the factors that influence the customer experience in the new retail business model; three hypotheses were built in this study, then tested. The quantitative approach uses a partial least square (PLS) application to obtain the data and measure the impact of each dimension on the new retail concept. The population in this study is Starbucks consumers who have used all online-offline channels and are living in Bandung West Java. Based on the research objectives, the conclusion from the research results is the establishment of a model that represents the relationship between consumer variables, convenience, communication, and customer experience. Based on the model validation results, consumers and communication are the factors that influence the customer experience in coffee shops online and offline in the new retail concept. The communication variable is the most significant variable that directly affects the customer experience.